A nearly zero energy building design method based on architecture form design for high solar exposure areas in China's severe cold and cold regions. (January 2022) - Li, En; Chen, Luyao; Zhang, Tianqi; Zhu, Jiangkun; Hou, Ren
Abstract: Located in a typical city with high solar exposure, Lhasa rural houses have the potential to achieve nearly zero consumption of heating energy by applying an efficient passive design method. Field survey, measurement and simulation were applied for the nearly zero energy building (nZEB) design method. After analyzing the architecture form design items of organizing heat collecting surfaces and buffer spaces, 5 out of 9 architecture form design items were proved to contribute to heating energy efficiency, including add-on direct solar gain system on width direction of north rooms, sunroom on roof, north sealed balcony, window-wall ratio (WWR) of south facade and layout shape. The architecture form design was proved to save nearly 80% of the heating energy, and the nZEB design method was proposed. The findings can serve as a guideline for the energy efficiency design for rural houses in high solar exposure area areas of China's severe cold and cold regions. Highlights: Proposed a nearly zero energy building design method based on architecture form. Organized heating collection surfaces and buffer spaces by architecture form design. Parameterized architecture form's heating energy saving effects. Measured the indoor thermal environment of a Tibetan house.